Evaluation of a dog with inflammatory mammary carcinoma using 18F‐2‐deoxy‐2‐fluoro‐d‐glucose positron emission tomography/computed tomography. Issue 4 (19th March 2022) - Koo, Yoonhoi; Yun, Taesik; Chae, Yeon; Lee, Dohee; Son, Mingyun; Ku, Dayoung; Kim, Hakhyun; Yang, Mhan‐Pyo; Kang, Byeong‐Teck
Abstract: Inflammatory mammary carcinoma is known to be aggressive, which makes thorough evaluation of the severity of tumour infiltration and metastasis important in determining a recommended treatment course. This case report describes the use of 18 F‐2‐deoxy‐2‐fluoro‐d ‐glucose positron emission tomography/computed tomography for evaluating the invasiveness and metastasis of inflammatory mammary carcinoma in a dog. Abstract : Inflammatory mammary carcinoma is known to be aggressive. It could be surgically resected after evaluating the severity of tumour infiltration and metastasis. This case report describes the use of 18 F‐2‐deoxy‐2‐fluoro‐d ‐glucose positron emission tomography/computed tomography for evaluating the invasiveness and metastasis of inflammatory mammary carcinoma in a dog.